Faktor â faktor yang Mempengaruhi Minat Berkunjung Mahasiswa ke Perpustakaan Universitas Kristen Petra - Widjaja, Johan; Halim, Siana (Jurnal Titra, 2014)
The library attendance at Petra Christian University is decreasing. We are interested in finding the factors affecting that attendance. In this study, we applied the LIBQUAL one of library quality measurements, and added some external and internal factors to answer the quest. Additionally, we also used the Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM) as tools for analyzing the constructs. As the result we found out that the factor that affecting library attendance is library as place, and the factor that doesnât affect library attendace is teacher motivation. Â